2021
DOI: 10.1016/j.ijscr.2021.106041
|View full text |Cite
|
Sign up to set email alerts
|

Impending cauda equina syndrome due to Kummell disease; A case report and literature review

Abstract: Introduction Kummell disease (KD) is a rare cause of vertebral fracture due to osteonecrosis. The natural history of the disease is characterized by a previous minor trauma, a subclinical window period, and then a symptomatic period presenting with disabling pain, kyphosis, or neurologic deficit. Importance As an important but rare cause of non-discogenic cauda equina syndrome. Case presentation Here, we report on a wheelchair-bound 28-years-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The main purpose of surgery is to relieve the nerve compression and the back pain in the patient. Therefore, the surgical method is decompression and fixation fusion ( 26 , 27 ). Lee et al reported that 10 patients with Kümmell disease and neural symptoms underwent posterior decompression, fixation, and fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of surgery is to relieve the nerve compression and the back pain in the patient. Therefore, the surgical method is decompression and fixation fusion ( 26 , 27 ). Lee et al reported that 10 patients with Kümmell disease and neural symptoms underwent posterior decompression, fixation, and fusion.…”
Section: Discussionmentioning
confidence: 99%